Mitigasi Banjir Di Wilayah Pertanian Dan Survei Pengetahuan Masyarakat Kabupaten Lombok Tengah Tentang Mitigasi Bencana Banjir - Marzuki, Marzuki (SOLID, 2023)
The aim of this research is to identify agricultural areas in the Central Lombok Regency that are vulnerable to flooding before the planting process of rice or other crops commences. This effort aims to mitigate flood risks by cleaning up the Watershed Areas (DAS) to prevent water overflow that may lead to flooding. Therefore, the cleanliness of the Watershed Areas is crucial, where the surrounding vegetation needs to be maintained without being too dense, avoiding blockage of water flow that could result in flood disasters. The method employed is quantitative, utilizing a direct survey approach to farmers at risk of flood impacts. The findings of this research are intended to provide knowledge to the community in disaster mitigation efforts before floods occur, particularly targeting the moderate category. Additionally, this study also aims to evaluate the level of community knowledge in flood mitigation during floods, which also falls within the moderate category. Furthermore, another objective is to assess community knowledge in post-flood mitigation, with an expectation of their knowledge level falling into the high category. Based on the survey data, there are 3 individuals or 5.36% of respondents categorized as having low knowledge, 49 individuals or 87.5% categorized as having moderate knowledge, and 4 individuals or 7.14% categorized as having high knowledge.